Biorational management of okra jassid (Amrasca devastans) (Progressive Agriculture, 2018)
An experiment was carried out to appraise the comparative efficacy of some biorationals against okra jassid at the Field Laboratory, Department of Entomology, Bangladesh Agricultural University, Mymensingh during January to June 2016. The experiment was accomplished using three botanical oils (Neem oil@ 2ml/L, Mahogany oil @2ml/L & Karanja oil @2ml/L) and four microbial insecticides (Spinosad @ 1ml/ L, Beauveria bassiana @ 1 g/ L, Buprofezin @ 2ml/L, Emamectin benzoate @ 1g/L) along with control. Among various biorationals the mean number of nymph plant-1 varied significantly (p